An exploratory qualitative study exploring GPs' and psychiatrists' perceptions of post‐traumatic stress disorder in postnatal women using a fictional case vignette. (29th November 2021) - Mortimer, Harriet; Habash‐Bailey, Haniah; Cooper, Maxwell; Ayers, Susan; Cooke, Jennifer; Shakespeare, Judy; Aslanyan, Daron; Ford, Elizabeth
Abstract: Postnatal post‐traumatic stress disorder (PTSD) affects 3%–4% of women who give birth. It is underdiagnosed and undertreated. Thus far, no studies have investigated doctors' perceptions of PTSD in postnatal women. We investigated whether GPs and psychiatrists perceive PTSD symptoms after birth to indicate pathology and what diagnosis and management they would offer. Semi‐structured interviews were conducted with six GPs and seven psychiatrists using a fictional vignette featuring a woman experiencing PTSD following a traumatic birth. A framework analysis approach was used. Despite half the GPs recognizing trauma‐related features in the vignette their most common diagnosis was postnatal depression whereas six of the seven psychiatrists identified PTSD. Management plans reflected this. Both GPs and psychiatrists lacked trust in timeliness of referrals to psychological services. Both suggested referral to specialist perinatal mental health teams. Results suggest women are unlikely to get a PTSD diagnosis during initial GP consultations, however the woman‐centred care proposed by GPs means that a trauma‐focussed diagnosis later in the care pathway was not ruled out. Further research is needed to confirm these findings, which suggest that an evidence base around best management for women with postnatal PTSD is sorely needed, especially to inform GP training.